Hubungan antara Olahraga dengan Tingkat Keparahan Hipertensi di Poliklinik Jantung RSUD Dr R. Koesma Tuban - Titik Sumiatin; Yasin Wahyurianto; Wahyu Tri Ningsih (STIKes Patria Husada Blitar, 2015)
Hypertention according WHO is systolic pulse > 140mmHg and dyastolic pulse >90mmHg which chronicle way. Complication of blood vessels is caused by hypertention, it causes Coronary hearth attack, Infark miokard, Stroke, and Renal failure (Gunawan, 2001). Based on early survey on 10 â€“ 14 march 2009th, there are 14 (25,4%) of 55 patiens are hypertention. Goal of research is to know relation between exercise and the mortal of hypertention at Poliklinik Jantung RSUD Dr. R Koesma Tuban. Design of research is analytic with cross sectional method. Population of research are 56 respondens and sample of research are 48 patient with hypertention. Sampling technique used stratified random sampling. Instrument to collecting data used questioner and observation, then tested by Spearman rank correlation test. Result of research is there isÂ connention between the exercise with the mortal hypertention level at Poliklinik Jantung RSUD Dr. R Koesma Tuban. It shown from 48 patient with hypertention. They are average exercise regularly and have low hyperlention level, in percentage 100%. The things give evidence that there is connection between the exercise with the mortal hypertention level. So, H1 is reseived in rank infact (0,000 < 0,05) and Ïspearman value = 0,000 significant 0.05. Exercise is important for hypertention. Because from research, exercise regularly can absorb and make lose Chollestrole precipitation in arthery.